Janji Negara Donor Tsunami Aceh Dalam Perspektif Hukum Intemasional - author: sefriani (Fakultas Hukum Universitas Islam Indonesia, 2005)
Signature, exchange of instruments or ratification will be binding If the text provides that these actions are to have that effect. A treaty which merely needs signatures from the parties, it will be legally binding to the parties by signing the treaty. However, for a treaty which needs ratification, signatures of the parties will not have a legal effect to the parties. The parties who have signed the treaty is only bound morally. Thus, the treaty will be legally binding to the parties, if the parties have ratified it.